The determining factors of attractiveness in urban tourism: a study in Mexico City, Buenos Aires, Bogota, and Lima - Sirkis, Gabriela (2022)
This research aims to examine the tourist recognition of the different attractions of the four most populous Spanish-speaking cities in Latin America: Mexico City, Buenos Aires, Bogotá, and Lima, and determine the factors that group these attractions and evaluate their degree of importance. Factor analysis technique was used to reduce the perceptions into relevant factors. The methodology used is quantitative, transversal, and non-experimental. The results indicate that the tourist attraction of a city has four main factors: the nucleus, the tourism ecosystem, Meetings, Incentives, Conventions and Exhibitions/Events (MICE) and shows, and the related services. The research has theoretical implications because it determines that tourists perceive attractions at four levels in these Latin American cities, each of which is made up of tourist attractions different from those mentioned in the literature. The research has practical implications, since officials and those responsible for tourism in Latin American cities can improve their plans by considering the factors of tourist attraction that generate a greater influx of tourists in the cities examined.